Preparation method of degradable high-barrier antibacterial film

By uniformly dispersing antibacterial particles in the prepolymer synthesis stage of the film material and synthesizing amidated PBAT-PLA copolymer, the problems of fluctuations in the antibacterial properties of the film material and low water-gas barrier properties are solved, and efficient antibacterial and barrier effects are achieved .

CN119463240APending Publication Date: 2025-02-18淮北矿业绿色化工新材料研究院有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411626581.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The antibacterial properties of existing film materials fluctuate greatly and have low moisture barrier properties, making it difficult to meet the needs of food packaging and plastic wrap.

Method used

The antibacterial and barrier properties of the film are improved by uniformly dispersing the antibacterial particles in the prepolymer synthesis stage and synthesizing the amidated PBAT-PLA copolymer through esterification and polycondensation reaction.

Benefits of technology

The uniform distribution of antibacterial particles is achieved, the antibacterial performance fluctuations are avoided, and the water-gas barrier properties of the film are improved, ensuring the effectiveness of food packaging and plastic wrap.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134894980000071
    Figure BDA0005134894980000071
  • Figure BDA0005134894980000081
    Figure BDA0005134894980000081
  • Figure BDA0005134894980000092
    Figure BDA0005134894980000092
Patent Text Reader

Abstract

The invention discloses a preparation method of a degradable high-barrier antibacterial film. The preparation method comprises the following steps: firstly, dispersing and dissolving antibacterial particles in a 1, 4-butanediol (BDO) or lactic acid (LA) solution to prepare an antibacterial particle dispersion liquid, and uniformly dispersing the antibacterial particles in a copolymer through an in-situ polymerization method. A prepolymer is synthesized by adopting a esterification method, diamine is added, polar amide groups are introduced into molecular chains, and through hydrogen bonds formed between the amide groups and hydrogen atoms, the interaction between the molecular chains is increased, and the barrier property is enhanced. An LA chain segment is introduced, an amidated PBAT-PLA copolymer is prepared through polycondensation, the copolymer serves as a compatilizer of PBAT and polylactic acid (PLA), the compatibility and barrier performance of the two polymers can be improved, and antibacterial performance is improved by introducing antibacterial particles. The antibacterial film prepared by the preparation method disclosed by the invention has excellent barrier property and uniform antibacterial property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an antibacterial film, in particular to a method for preparing a degradable high-barrier antibacterial film. Background Art

[0002] Polyethylene is commonly used as a raw material for food packaging bags and cling film in the market. This difficult-to-degrade film will cause serious pollution to the environment after being discarded. It is necessary to seek a packaging material that can be decomposed by microorganisms under specific conditions to replace non-biodegradable petroleum-based polymer materials. In this context, polybutylene adipate / terephthalate (PBAT) film came into being as a substitute for polyethylene film. PBAT has good biodegradability and can be completely degraded under the action of composting without leaving any residue that is harmful to the environment. In addition, PBAT has good flexibility, impact resistance, and thermal stability, and its texture is soft and transparent. Its mechanical properties such as stretching and elongation are similar to those of low-density polyethylene. However, PBAT has low oxygen and water vapor barrier properties, and its performance as food packaging bags and cling film is not as good as polyethylene film.

[0003] In addition, the PBAT material itself does not have antibacterial ability. In order to improve its antibacterial performance, Chinese patent CN108752884A discloses a highly antibacterial PLA_PBAT material and its preparation method and application. The method is to mix PLA, PBAT and antibacterial inorganic fillers at room temperature, melt extrude or mix and granulate to obtain a highly antibacterial PLA / PBAT material. However, this method of directly adding antibacterial fillers to polymers is prone to filler agglomeration and uneven dispersion, resulting in large fluctuations in the antibacterial performance of different parts of the film product and low local antibacterial performance. Therefore, it is urgent to develop a degradable composite film material with small fluctuations in antibacterial performance and excellent barrier properties. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a degradable high-barrier antibacterial film to solve the problem that the antibacterial properties of existing film materials fluctuate greatly and the water vapor barrier performance is low.

[0005] Technical solution: The method for preparing a degradable high-barrier antibacterial film of the present invention comprises the following steps:

[0006] (1) dispersing antibacterial particles in 1,4-butanediol at a first ratio to obtain a first dispersion, mixing the first dispersion, a first catalyst and terephthalic acid, and then performing an esterification reaction to obtain a first prepolymer;

[0007] (2) dispersing the antibacterial particles in 1,4-butanediol at a second ratio to obtain a second dispersion, mixing the second dispersion, the first catalyst and adipic acid, and then subjecting the mixture to an esterification reaction to obtain a second prepolymer;

[0008] (3) dispersing the antibacterial particles in lactic acid to obtain a third dispersion, mixing the third dispersion with a second catalyst and subjecting the mixture to an esterification reaction to obtain a lactic acid prepolymer;

[0009] (4) mixing the first prepolymer, the second prepolymer, the diamine and the first catalyst and performing an esterification reaction to obtain an amidated BAT prepolymer;

[0010] (5) mixing the amidated BAT prepolymer, the lactic acid prepolymer and the third catalyst and performing a polycondensation reaction to obtain an amidated PBAT-PLA copolymer;

[0011] (6) Polybutylene adipate / terephthalate, polylactic acid, amidated PBAT-PLA copolymer, and antioxidant are plasticized and granulated by twin-screw extrusion and then blown into a biodegradable high-barrier antibacterial film.

[0012] The present invention first disperses and dissolves the antibacterial particles in 1,4-butanediol (BDO) or lactic acid (LA) solution to obtain an antibacterial particle dispersion, and then uniformly disperses the antibacterial particles in the copolymer by an in-situ polymerization method. The prepolymer is synthesized by the fractionation esterification method, and diamine is added to introduce polar amide groups into the molecular chain. The hydrogen bonds formed between the amide groups and hydrogen atoms increase the interaction between the molecular chains and enhance the barrier properties. The LA segment is introduced and polycondensed to obtain an amido PBAT-PLA copolymer. The copolymer can improve the compatibility and barrier properties of the two polymers as a compatibilizer for PBAT and polylactic acid (PLA), and the introduction of antibacterial particles improves the antibacterial properties.

[0013] Preferably, in steps (1)-(3), the antibacterial particles are at least one of nano zinc oxide, anhydrous copper sulfate, and nano silver; and the concentration ratio of the antibacterial particles in the first dispersion: the antibacterial particles in the second dispersion: the antibacterial particles in the third dispersion is 1-3:1-4:1-3.

[0014] Preferably, in step (1), the molar ratio of terephthalic acid to 1,4-butanediol is 1:1-3; the esterification reaction conditions are esterification reaction at 195-215° C. for 2-5 hours under a pressure of 50-80 kPa; and the amount of the first catalyst added is 0.1-0.25% of the sum of the weight of terephthalic acid and the first dispersion.

[0015] Preferably, in step (2), the molar ratio of adipic acid to 1,4-butanediol is 1:1-2, and the esterification reaction conditions are esterification reaction at 160-190°C under a pressure of 50-80 kPa for 1-3 hours; and the amount of the first catalyst added is 0.1-0.25% of the sum of the weight of adipic acid and the second dispersion.

[0016] Preferably, in step (3), the esterification reaction conditions are esterification reaction at 140-160° C. under a pressure of 50-80 kPa for 1-3 hours; and the amount of the second catalyst added is 0.1-0.25 wt % of the lactic acid.

[0017] Preferably, in step (4), the mass ratio of the first prepolymer, the second prepolymer and the diamine is 1-4:1:0.002-0.25; the diamine includes at least one of butanediamine, pentamethylenediamine, hexamethylenediamine and decamethylenediamine; the esterification reaction conditions are esterification reaction at 180-220°C under a pressure of 50-80 kPa for 1-3 hours; and the amount of the first catalyst added is 0.1-0.25% of the sum of the weight of the first prepolymer, the second prepolymer and the diamine.

[0018] Preferably, in step (5), the polycondensation reaction method is to mix the amidated BAT prepolymer, the lactic acid prepolymer, the third catalyst, triphenyl phosphate and the antioxidant in a weight ratio of 1-10:1:0.002-0.0275:0.002-0.033:0.002-0.055, and then polycondense at 230-250°C under a pressure of 10-25 kPa for 2-6 hours.

[0019] Preferably, the first ratio is 0.5-10:100 of the mass ratio of antibacterial particles to 1,4-butanediol, the second ratio is 0.5-10:100 of the mass ratio of antibacterial particles to 1,4-butanediol, and the mass ratio of antibacterial particles to lactic acid in the third dispersion is 0.5-10:100.

[0020] Preferably, in step (6), the weight ratio of poly(butylene adipate / terephthalate):poly(lactic acid):amidated PBAT-PLA copolymer:antioxidant is 100:5-30:1-10:0.1-0.5; and the twin-screw extrusion temperature is 150-180°C.

[0021] Preferably, in steps (1), (2) and (4), the first catalyst is one or more of tetrabutyl titanate, zinc oxide, zinc hydroxide, zinc carbonate, calcium hydroxide, calcium carbonate, barium hydroxide and barium carbonate; in step (3), the second catalyst is one or more of anhydrous zinc acetate, tin isooctanoate, stannous isooctanoate, stannous oxide, stannous chloride and stannous oxalate; in step (5), the third catalyst is one or more of antimony trioxide, tetrabutyl titanate, tetraphenyltin and stannous octoate.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0023] The present invention can make the antibacterial particles evenly distributed in the composite material by adding antibacterial particles in the prepolymer synthesis stage, avoiding the problem of large fluctuations in the antibacterial performance of the film caused by uneven distribution of antibacterial particles. Secondly, by reasonably controlling the weight ratio of the antibacterial particles in the first dispersion, the second dispersion and the third dispersion, the problem of reduced barrier performance of the composite material final product caused by adding antibacterial particles in the prepolymer synthesis stage can be avoided, so that the final product can have both uniform antibacterial performance and high water vapor barrier performance. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below.

[0025] Embodiment 1: A method for preparing a degradable high barrier antibacterial film, comprising the following steps:

[0026] (1) Nano zinc oxide is dispersed in 1,4-butanediol at a concentration of 5wt% to obtain a first dispersion; the first dispersion, tetrabutyl titanate and terephthalic acid are added into a reaction kettle at a molar ratio of terephthalic acid to 1,4-butanediol of 1:2, and mixed; and an esterification reaction is carried out at 205°C under a pressure of 65kPa for 3h to obtain a first prepolymer; the amount of tetrabutyl titanate added is 0.18% of the sum of the weight of terephthalic acid and the first dispersion.

[0027] (2) Nano zinc oxide is dispersed in 1,4-butanediol at a concentration of 5 wt% to obtain a second dispersion, the second dispersion, tetrabutyl titanate and adipic acid are mixed at a molar ratio of adipic acid to 1,4-butanediol of 1:1.5, and an esterification reaction is carried out at 175° C. for 2 h under a pressure of 65 kPa to obtain a second prepolymer; the amount of tetrabutyl titanate added is 0.15% of the sum of the weight of adipic acid and the second dispersion.

[0028] (3) dispersing nano zinc oxide in lactic acid at a concentration of 5 wt % to obtain a third dispersion, mixing the third dispersion with anhydrous zinc acetate, and subjecting the mixture to an esterification reaction at 150° C. for 2 h at a pressure of 65 kPa to obtain a lactic acid prepolymer; the amount of anhydrous zinc acetate added is 0.18 wt % of the lactic acid.

[0029] (4) After mixing the first prepolymer, the second prepolymer, pentamethylenediamine and tetrabutyl titanate, an esterification reaction is carried out at 200° C. under a pressure of 65 kPa for 2 hours to obtain an amidated BAT prepolymer; the mass ratio of the first prepolymer, the second prepolymer and pentamethylenediamine is 2.5:1:0.12; the amount of tetrabutyl titanate added is 0.18% of the sum of the weight of the first prepolymer, the second prepolymer and the diamine.

[0030] (5) mixing an amidated BAT prepolymer, a lactic acid prepolymer, antimony trioxide, triphenyl phosphate and an antioxidant 1010 in a weight ratio of 5:1:0.016:0.01:0.03, and polycondensing the mixture at 240° C. for 4 h under a pressure of 15 kPa to obtain an amidated PBAT-PLA copolymer;

[0031] (6) After adding the raw materials in a weight ratio of 100:18:7:0.3 of poly(butylene adipate / terephthalate):poly(lactic acid):amidoated PBAT-PLA copolymer:antioxidant 1010, the raw materials were plasticized and granulated by twin-screw extrusion at 170°C and then blown by a film blowing machine to obtain a 0.2 mm thick PBAT-PLA antibacterial film.

[0032] Embodiment 2: A method for preparing a degradable high barrier antibacterial film, comprising the following steps:

[0033] (1) Nano zinc oxide is dispersed in 1,4-butanediol at a concentration of 3 wt% to obtain a first dispersion; the first dispersion, calcium hydroxide and terephthalic acid are added into a reaction kettle at a molar ratio of terephthalic acid to 1,4-butanediol of 1:1, and mixed; and an esterification reaction is carried out at 195° C. for 2 h under a pressure of 50 kPa to obtain a first prepolymer; the amount of calcium hydroxide added is 0.1% of the sum of the weight of terephthalic acid and the first dispersion.

[0034] (2) dispersing nano zinc oxide in 1,4-butanediol at a concentration of 4 wt% to obtain a second dispersion, mixing the second dispersion, calcium hydroxide and adipic acid at a molar ratio of adipic acid to 1,4-butanediol of 1:1, and subjecting the mixture to an esterification reaction at 160° C. for 1 h at a pressure of 50 kPa to obtain a second prepolymer; the amount of calcium hydroxide added is 0.1% of the sum of the weight of the adipic acid and the second dispersion.

[0035] (3) dispersing nano zinc oxide in lactic acid at a concentration of 3 wt % to obtain a third dispersion, mixing the third dispersion with tin isooctanoate, and subjecting the mixture to an esterification reaction at 140° C. for 1 h at a pressure of 50 kPa to obtain a lactic acid prepolymer; the amount of tin isooctanoate added is 0.1 wt % of the lactic acid.

[0036] (4) After mixing the first prepolymer, the second prepolymer, diamine and calcium hydroxide, an esterification reaction is carried out at 180° C. under a pressure of 50 kPa for 1 hour to obtain an amidated BAT prepolymer; the mass ratio of the first prepolymer, the second prepolymer and diamine is 1:1:0.002; the amount of calcium hydroxide added is 0.1% of the sum of the weight of the first prepolymer, the second prepolymer and the diamine.

[0037] (5) mixing the amidated BAT prepolymer, the lactic acid prepolymer, tetrabutyl titanate, triphenyl phosphate and the antioxidant 1010 in a weight ratio of 1:1:0.002:0.002:0.002, and polycondensing the mixture at 230° C. for 2 h under a pressure of 10 kPa to obtain an amidated PBAT-PLA copolymer;

[0038] (6) After adding the raw materials in a weight ratio of 100:5:1:0.1 of poly(butylene adipate / terephthalate):poly(lactic acid):amidoated PBAT-PLA copolymer:antioxidant 1010, the raw materials were plasticized and granulated by twin-screw extrusion at 150°C and then blown by a film blowing machine to obtain a 0.2 mm thick PBAT-PLA antibacterial film.

[0039] Embodiment 3: A method for preparing a degradable high barrier antibacterial film, comprising the following steps:

[0040] (1) Nano zinc oxide is dispersed in 1,4-butanediol at a concentration of 2wt% to obtain a first dispersion, the first dispersion, barium carbonate and terephthalic acid are added into a reaction kettle at a molar ratio of terephthalic acid to 1,4-butanediol of 1:3, and mixed, and then esterified at 215°C under a pressure of 80kPa for 5h to obtain a first prepolymer; the amount of barium carbonate added is 0.25% of the sum of the weight of terephthalic acid and the first dispersion.

[0041] (2) dispersing nano zinc oxide in 1,4-butanediol at a concentration of 3 wt% to obtain a second dispersion, mixing the second dispersion, barium carbonate and adipic acid at a molar ratio of adipic acid to 1,4-butanediol of 1:2, and subjecting the mixture to an esterification reaction at 190° C. for 3 h at a pressure of 80 kPa to obtain a second prepolymer; the amount of barium carbonate added is 0.25% of the sum of the weight of the adipic acid and the second dispersion.

[0042] (3) dispersing nano zinc oxide in lactic acid at a concentration of 2 wt% to obtain a third dispersion, mixing the third dispersion and stannous oxide, and subjecting the mixture to an esterification reaction at 160° C. for 3 h under a pressure of 80 kPa to obtain a lactic acid prepolymer; the amount of stannous oxide added is 0.25 wt% of the lactic acid.

[0043] (4) After mixing the first prepolymer, the second prepolymer, hexamethylenediamine and barium carbonate, an esterification reaction is carried out at 220° C. under a pressure of 80 kPa for 3 hours to obtain an amidated BAT prepolymer; the mass ratio of the first prepolymer, the second prepolymer and hexamethylenediamine is 4:1:0.25; the amount of barium carbonate added is 0.25% of the sum of the weight of the first prepolymer, the second prepolymer and the diamine.

[0044] (5) mixing the amidated BAT prepolymer, the lactic acid prepolymer, tetraphenyltin, triphenyl phosphate and the antioxidant 1010 in a weight ratio of 10:1:0.0275:0.033:0.055, and polycondensing the mixture at 250° C. for 6 h under a pressure of 25 kPa to obtain an amidated PBAT-PLA copolymer;

[0045] (6) After adding the raw materials in a weight ratio of 100:30:10:0.5 of poly(butylene adipate / terephthalate):poly(lactic acid):amidoated PBAT-PLA copolymer:antioxidant 1010, the raw materials were plasticized and granulated by twin-screw extrusion at 180°C and then blown by a film blowing machine to obtain a 0.2 mm thick PBAT-PLA antibacterial film.

[0046] Embodiment 4: A method for preparing a degradable high barrier antibacterial film, comprising the following steps:

[0047] (1) Nanosilver is dispersed in 1,4-butanediol at a concentration of 10 wt% to obtain a first dispersion; the first dispersion, zinc carbonate and terephthalic acid are added to a reaction kettle at a molar ratio of terephthalic acid to 1,4-butanediol of 1:2, and mixed; and the mixture is esterified at 200° C. for 4 h under a pressure of 70 kPa to obtain a first prepolymer; the amount of zinc carbonate added is 0.15% of the sum of the weight of terephthalic acid and the first dispersion.

[0048] (2) dispersing nanosilver in 1,4-butanediol at a concentration of 3.3 wt% to obtain a second dispersion; mixing the second dispersion, zinc carbonate and adipic acid at a molar ratio of adipic acid to 1,4-butanediol of 1:2; and subjecting the mixture to an esterification reaction at 180° C. for 2 h at a pressure of 80 kPa to obtain a second prepolymer; the amount of zinc carbonate added is 0.2% of the sum of the weight of the adipic acid and the second dispersion.

[0049] (3) dispersing nanosilver in lactic acid at a concentration of 10 wt % to obtain a third dispersion, mixing the third dispersion with stannous chloride, and subjecting the mixture to an esterification reaction at 150° C. for 3 h under a pressure of 70 kPa to obtain a lactic acid prepolymer; the amount of stannous chloride added is 0.2 wt % of the lactic acid.

[0050] (4) After mixing the first prepolymer, the second prepolymer, decanediamine and zinc carbonate, an esterification reaction is carried out at 210° C. under a pressure of 80 kPa for 2 hours to obtain an amidated BAT prepolymer; the mass ratio of the first prepolymer, the second prepolymer and decanediamine is 3:1:0.002; the amount of zinc carbonate added is 0.25% of the sum of the weight of the first prepolymer, the second prepolymer and the diamine.

[0051] (5) mixing the amidated BAT prepolymer, lactic acid prepolymer, stannous octoate, triphenyl phosphate and antioxidant 1010 in a weight ratio of 4:1:0.062:0.013:0.015, and polycondensing the mixture at 250° C. for 4 h under a pressure of 15 kPa to obtain an amidated PBAT-PLA copolymer;

[0052] (6) After adding the raw materials in a weight ratio of 100:20:3:0.3 of poly(butylene adipate / terephthalate):poly(lactic acid):amidoated PBAT-PLA copolymer:antioxidant 1010, the raw materials were plasticized and granulated by twin-screw extrusion at 170°C and then blown by a film blowing machine to obtain a 0.2 mm thick PBAT-PLA antibacterial film.

[0053] Embodiment 5: A method for preparing a degradable high barrier antibacterial film, comprising the following steps:

[0054] (1) Anhydrous copper sulfate is dispersed in 1,4-butanediol at a concentration of 0.5 wt% to obtain a first dispersion; the first dispersion, barium hydroxide and terephthalic acid are added into a reaction kettle at a molar ratio of terephthalic acid to 1,4-butanediol of 1:3, and mixed; and an esterification reaction is carried out at 195° C. for 2 h under a pressure of 80 kPa to obtain a first prepolymer; the amount of barium hydroxide added is 0.1% of the sum of the weight of terephthalic acid and the first dispersion.

[0055] (2) Anhydrous copper sulfate is dispersed in 1,4-butanediol at a concentration of 2 wt% to obtain a second dispersion, the second dispersion, barium hydroxide and adipic acid are mixed at a molar ratio of adipic acid to 1,4-butanediol of 1:1, and an esterification reaction is carried out at 170° C. for 3 h under a pressure of 50 kPa to obtain a second prepolymer; the amount of barium hydroxide added is 0.1% of the sum of the weight of the adipic acid and the second dispersion.

[0056] (3) Nano zinc oxide, anhydrous copper sulfate and nano silver are dispersed in lactic acid at a concentration of 1.5 wt % to obtain a third dispersion; the third dispersion is mixed with stannous oxalate, and then subjected to an esterification reaction at 155° C. for 3 h under a pressure of 50 kPa to obtain a lactic acid prepolymer; the amount of stannous oxalate added is 0.1 wt % of the lactic acid.

[0057] (4) After mixing the first prepolymer, the second prepolymer, pentamethylenediamine and barium hydroxide, an esterification reaction is carried out at 210° C. under a pressure of 70 kPa for 3 hours to obtain an amidated BAT prepolymer; the mass ratio of the first prepolymer, the second prepolymer and pentamethylenediamine is 4:1:0.01; the amount of barium hydroxide added is 0.1% of the sum of the weight of the first prepolymer, the second prepolymer and the diamine.

[0058] (5) mixing the amidated BAT prepolymer, the lactic acid prepolymer, the tetrabutyl titanate, the triphenyl phosphate and the antioxidant 1010 in a weight ratio of 7:1:0.0275:0.002:0.002, and polycondensing the mixture at 230° C. for 6 h under a pressure of 15 kPa to obtain an amidated PBAT-PLA copolymer;

[0059] (6) After adding the raw materials in a weight ratio of 100:25:6:0.4 of poly(butylene adipate / terephthalate):poly(lactic acid):amidoated PBAT-PLA copolymer:antioxidant 1010, the raw materials were plasticized and granulated by twin-screw extrusion at 160°C, and then film-blown by a film blowing machine to obtain a 0.2 mm thick PBAT-PLA antibacterial film.

[0060] Comparative Example 1: The rest is the same as Example 1, except that:

[0061] No nano zinc oxide is added in steps (1), (2) and (3), and the same amount of nano zinc oxide is put into a twin-screw extruder together with other materials for granulation in step (6), and the antibacterial film is prepared by film blowing.

[0062] Comparative Examples 2-9: The rest are the same as Example 1, except that:

[0063] Different antibacterial film samples were prepared by taking the concentration of antibacterial particles in the first dispersion, the concentration of antibacterial particles in the second dispersion, and the concentration of antibacterial particles in the third dispersion in steps (1) to (3) as variables. The concentration ratios in each example are shown in Table 1:

[0064] Table 1 Concentration ratio settings for each comparative example

[0065]

[0066] The antibacterial film samples prepared in Examples 1-5 and Comparative Examples 1-9 were tested as follows:

[0067] 1. Degradation performance test

[0068] The film samples were subjected to corresponding degradation experiments in water, soil burial, and CALB enzyme conditions. The samples were weighed before the test and 10 weeks after the test, and the mass loss rate was calculated. The results are as follows:

[0069] Table 2 Degradation performance test results of different antibacterial films

[0070] Group Hydrolysis mass loss (%) Soil burial mass loss (%) Enzymatic mass loss (%) Example 1 3.7 2.1 8.9 Example 2 3.4 1.9 7.7 Example 3 3.1 1.8 8.4 Example 4 3.5 1.7 8.1 Example 5 3.3 1.5 7.9 Comparative Example 1 3.2 1.2 8.5 Comparative Example 2 3.0 1.1 7.4 Comparative Example 3 2.8 1.7 8.2 Comparative Example 4 3.4 1.8 8.0 Comparative Example 5 3.3 1.6 8.3 Comparative Example 6 3.1 1.5 7.9 Comparative Example 7 3.5 1.4 8.2 Comparative Example 8 3.2 1.9 8.8 Comparative Example 9 3.1 1.7 8.5

[0071] It can be seen from the results in Table 2 that the antibacterial film prepared in the present invention has good degradability, and the addition of antibacterial particles does not have a significant effect on the degradation performance of the film material.

[0072] 2. Barrier performance test

[0073] The water vapor barrier rate of the film was tested using a water vapor transmission rate tester to measure the water vapor transmission rate. The oxygen transmission rate of the film was tested using a differential pressure gas permeation tester to measure the oxygen transmission coefficient.

[0074] The results are shown in Table 3:

[0075] Table 3 Barrier performance test results of different antibacterial films

[0076]

[0077] In the results of Table 3, the barrier performance of Comparative Example 1 is significantly lower than that of Example 1, indicating that the antibacterial particles are easily mixed into the composite material during the extrusion stage, resulting in uneven dispersion, and the agglomerated antibacterial particles significantly reduce the water vapor barrier performance of the film, resulting in a negative impact. The barrier performance of Comparative Examples 2-9 is also significantly lower than that of Example 1, indicating that the selection of the concentration of antibacterial particles in the first dispersion, the second dispersion, and the third dispersion has a great influence on the barrier performance of the film. The main reason is that the antibacterial particles added to the prepolymer will interfere with the esterification reaction of the first prepolymer, the second prepolymer and the diamine at the wrong concentration, resulting in an increase in the byproducts of the amidated BAT prepolymer, and a significant decrease in the product yield and purity, which in turn leads to the loss of the barrier performance improvement effect of the amidated PBAT-PLA copolymer obtained by subsequent polycondensation.

[0078] 3. Antibacterial performance test

[0079] The antibacterial properties of the film were determined by the plate count method. A liquid culture medium with a mass ratio of distilled water: agar: peptone: NaCl: beef extract of 100:2:1:0.5:0.5 was prepared. After sterilization, a volume ratio of 1% Escherichia coli was inoculated on the culture dish. 1g of the sample film was weighed, and after ultraviolet sterilization, it was immersed in a 2ml liquid culture dish. After culturing in a constant temperature shaker at 37°C for 18h, 20μL was spread on the agar solid culture medium and cultured for 24h. After dilution, the count was counted, and the final number of remaining viable bacteria was calculated. According to the formula: Calculate the antibacterial rate. According to the experiment, the number of viable bacteria in the blank sample is 4.3×10 9 indivual;

[0080] The sampling of film samples is based on the following rules:

[0081] The test samples were cut from different sites on the same film at least 1m apart, and 10 sites were cut from each film for repeated experiments. The test results are expressed as mean ± SD values:

[0082] Table 4 Antibacterial performance test results of different antibacterial films

[0083]

[0084] As can be seen from the results in Table 4, the average antibacterial rate of Comparative Example 1 is lower than that of Example 1, and the SD value is larger, indicating that the antibacterial particles mixed in the extrusion stage cannot achieve a stable antibacterial effect, and the uneven dispersion of the antibacterial particles in the film leads to large differences in the antibacterial properties of different sites, so the SD value is large. The antibacterial properties and uniformity of Comparative Examples 2-9 are not significantly different from those of Example 1, indicating that the inorganic antibacterial particles can be dispersed and added during the preparation of the prepolymer to meet the requirements of uniform dispersion, so the antibacterial effect is stable and uniform, and the concentration change of the antibacterial ions in the dispersion does not affect the improvement of the antibacterial stability.

Claims

1. A method for preparing a degradable high barrier antibacterial film, characterized in that: The steps include: (1) dispersing antibacterial particles in 1,4-butanediol at a first ratio to obtain a first dispersion, mixing the first dispersion, a first catalyst and terephthalic acid, and then performing an esterification reaction to obtain a first prepolymer; (2) dispersing the antibacterial particles in 1,4-butanediol at a second ratio to obtain a second dispersion, mixing the second dispersion, the first catalyst and adipic acid, and then subjecting the mixture to an esterification reaction to obtain a second prepolymer; (3) dispersing the antibacterial particles in lactic acid to obtain a third dispersion, mixing the third dispersion with a second catalyst and subjecting the mixture to an esterification reaction to obtain a lactic acid prepolymer; (4) mixing the first prepolymer, the second prepolymer, the diamine and the first catalyst and performing an esterification reaction to obtain an amidated BAT prepolymer; (5) mixing the amidated BAT prepolymer, the lactic acid prepolymer and the third catalyst and performing a polycondensation reaction to obtain an amidated PBAT-PLA copolymer; (6) Polybutylene adipate / terephthalate, polylactic acid, amidated PBAT-PLA copolymer, and antioxidant are plasticized and granulated by twin-screw extrusion and then blown into a biodegradable high-barrier antibacterial film.

2. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In steps (1)-(3), the antibacterial particles are at least one of nano zinc oxide, anhydrous copper sulfate, and nano silver; and the concentration ratio of the antibacterial particles in the first dispersion: the antibacterial particles in the second dispersion: the antibacterial particles in the third dispersion is 1-3:1-4:1-3.

3. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In step (1), the molar ratio of terephthalic acid to 1,4-butanediol is 1:1-3; the esterification reaction conditions are esterification reaction at 195-215° C. for 2-5 hours under a pressure of 50-80 kPa; and the amount of the first catalyst added is 0.1-0.25% of the sum of the weight of terephthalic acid and the first dispersion.

4. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In step (2), the molar ratio of adipic acid to 1,4-butanediol is 1:1-2, and the esterification reaction conditions are esterification reaction at 160-190°C under a pressure of 50-80 kPa for 1-3 hours; the amount of the first catalyst added is 0.1-0.25% of the sum of the weight of adipic acid and the second dispersion.

5. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In step (3), the esterification reaction conditions are esterification reaction at 140-160° C. under a pressure of 50-80 kPa for 1-3 hours; and the amount of the second catalyst added is 0.1-0.25 wt % of the lactic acid.

6. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In step (4), the mass ratio of the first prepolymer, the second prepolymer and the diamine is 1-4:1:0.002-0.25; the diamine includes at least one of butanediamine, pentanediamine, hexamethylenediamine and decanediamine; the esterification reaction conditions are esterification reaction at 180-220°C under a pressure of 50-80 kPa for 1-3 hours; the amount of the first catalyst added is 0.1-0.25% of the sum of the weight of the first prepolymer, the second prepolymer and the diamine.

7. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In step (5), the polycondensation reaction method is to mix the amidated BAT prepolymer, the lactic acid prepolymer, the third catalyst, triphenyl phosphate and the antioxidant in a weight ratio of 1-10:1:0.002-0.0275:0.002-0.033:0.002-0.055, and then polycondense at 230-250°C under a pressure of 10-25 kPa for 2-6 hours.

8. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: The first ratio is 0.5-10:100 of the mass ratio of antibacterial particles to 1,4-butanediol, the second ratio is 0.5-10:100 of the mass ratio of antibacterial particles to 1,4-butanediol, and the mass ratio of antibacterial particles to lactic acid in the third dispersion is 0.5-10:

100.

9. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In step (6), the weight ratio of poly(butylene adipate / terephthalate):poly(lactic acid):amidated PBAT-PLA copolymer:antioxidant is 100:5-30:1-10:0.1-0.5; and the twin-screw extrusion temperature is 150-180°C.

10. The method for preparing the degradable high barrier antibacterial film according to claim 1, characterized in that: In steps (1), (2) and (4), the first catalyst is one or more of tetrabutyl titanate, zinc oxide, zinc hydroxide, zinc carbonate, calcium hydroxide, calcium carbonate, barium hydroxide and barium carbonate; in step (3), the second catalyst is one or more of anhydrous zinc acetate, tin isooctanoate, stannous isooctanoate, stannous oxide, stannous chloride and stannous oxalate; in step (5), the third catalyst is one or more of antimony trioxide, tetrabutyl titanate, tetraphenyltin and stannous octoate.

Citation Information

Patent Citations

  • Highly antibacterial PLA (polylactic acid) / PBAT (polybutylene adipate terephthalate) material as well as preparation method and application thereof

    CN108752884A